2019
DOI: 10.29309/tpmj/2019.26.06.3605
|View full text |Cite
|
Sign up to set email alerts
|

A novel modality to cure early glottic carcinoma

Abstract: Introduction: The current practice standards demand achievement of cure along with preservation of voice and laryngeal anatomy. The recommended approaches for early stage glottic carcinoma are both laser surgery (LS) as well as radiotherapy (RT). Both modalities having some merits as well as demerits. So the objective of the study is to compare the outcome of early glottic cancer patients having laser resection with the patients who received radiation therapy. Study Design: Cross sectional study. Setting: Ziau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This is consistent with study conducted at southern Punjab Pakistan. [8][9][10][11] In our study mostly the patients belong to age group 30-40yrs with slight increase in males to female ratio in Pakistan and abroad too. The age group and male to female ratio is consistent with many studies.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This is consistent with study conducted at southern Punjab Pakistan. [8][9][10][11] In our study mostly the patients belong to age group 30-40yrs with slight increase in males to female ratio in Pakistan and abroad too. The age group and male to female ratio is consistent with many studies.…”
Section: Discussionmentioning
confidence: 89%
“…The age group and male to female ratio is consistent with many studies. [8][9][10][11][12] On the contrary Riaz et al has found laryngeal cancer to be the disease of elderly with increasing male preponderance. 10 In US this incidence among males has been decreased from 12:1 to 5:1 over period of ten years.…”
Section: Discussionmentioning
confidence: 99%